2008
DOI: 10.1371/journal.pone.0003493
|View full text |Cite
|
Sign up to set email alerts
|

Extended Driving Impairs Nocturnal Driving Performances

Abstract: Though fatigue and sleepiness at the wheel are well-known risk factors for traffic accidents, many drivers combine extended driving and sleep deprivation. Fatigue-related accidents occur mainly at night but there is no experimental data available to determine if the duration of prior driving affects driving performance at night. Participants drove in 3 nocturnal driving sessions (3–5am, 1–5am and 9pm–5am) on open highway. Fourteen young healthy men (mean age [±SD] = 23.4 [±1.7] years) participated Inappropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
66
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 38 publications
6
66
2
1
Order By: Relevance
“…These factors are known to impair driving ability and induce subjective feelings of tiredness, slowed reaction times, lapses of attention to critical details and performance deterioration [2023]. As a result, sleep- and EDS-related MVAs are more likely to occur among professional male drivers than in males in the general population [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…These factors are known to impair driving ability and induce subjective feelings of tiredness, slowed reaction times, lapses of attention to critical details and performance deterioration [2023]. As a result, sleep- and EDS-related MVAs are more likely to occur among professional male drivers than in males in the general population [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing work suggests that time at the wheel may be an important additional factor. Sagaspe et al (2008) have demonstrated pronounced such effects on line crossings and KSS when driving at night 13) . Also, while of great practical importance, studies of driving may not be representative of other tasks common in industry, health care and service.…”
mentioning
confidence: 96%
“…However, such studies have been carried out with night driving and the effects have been pronounced [65,66].…”
Section: Performance Measuresmentioning
confidence: 99%